Rodzina i sprawy rodzinne w staropolskich pismach polemicznych - Kamieniecki, Jan (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2016)
The article presents ways of using motives related to family matters in Old Polish documents written by catholic and Protestant polemicists in both metaphorical and reality oriented content. As the analysed materials shows it was a common practice to use family related motives in religious polemics and to describe real or fictitious pathological phenomena. However, there is no a positive vision of marriage and family in the discussed polemic works. Recalling phenomena unacceptable for the society of that period was aimed at creating a proper image of a religious opponent. However, it led to significant simplification of theological argumentation.